1969
DOI: 10.1111/j.1469-8986.1969.tb02909.x
|View full text |Cite
|
Sign up to set email alerts
|

The Heart Rate Response to a Brief Auditory and Visual Stimulus

Abstract: The adult heart rate (HR) response was studied in 18 male subjects following a series of 10 tones and 10 light flashes. Both stimuli were of moderate intensity (54 db and 8.0 ml) and had rise times of 30 milliseconds. The tone evoked a predominantly acceleratory response and no decrement with repetition. Initially, the light flash evoked a predominantly deceleratory response which changed to one of acceleration as the stimulus was repeated. Analysis of respiration revealed that an increase in rate and amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…The complex HR response to our moderate auditory stimulus was very similar to those recently reported by other investigators using stimuli of various intensities (40-80 dB), frequencies, and rise times (Roessler et al, 1969;Raskin et al, 1969;Smith & Strawbridge, 1969;Connor & Lang, 1969). No obvious relation was observed between HR response pattern and respiration changes in our study or by others (Roessler et al, 1969;Connor & Lang, 1969).…”
Section: Response and Prestimulus Levelsupporting
confidence: 91%
“…The complex HR response to our moderate auditory stimulus was very similar to those recently reported by other investigators using stimuli of various intensities (40-80 dB), frequencies, and rise times (Roessler et al, 1969;Raskin et al, 1969;Smith & Strawbridge, 1969;Connor & Lang, 1969). No obvious relation was observed between HR response pattern and respiration changes in our study or by others (Roessler et al, 1969;Connor & Lang, 1969).…”
Section: Response and Prestimulus Levelsupporting
confidence: 91%
“…Besides analyzing the nature of ECG signal, many scientists have tried to analyze the influence of different kinds of external stimulation on heart activity. The works reported on analyzing the influence of auditory123, visual456 and olfactory stimuli789 are noteworthy to mention.…”
mentioning
confidence: 99%
“…Similarly, Klorman, Weissberg, and Wisenfeld (1977) found differences in the ECR to affective stimuli but no differences in respiration. Studies that have suggested respiratory-mediated ECRs have tended to report short-latency accelerative startle responses accompanied by inspiratory gasps (Graham & Clifton, 1966;Smith & Strawbridge, 1969). Hence, it would appear that decelerative responses are independent of respiratory changes.…”
Section: Discussionmentioning
confidence: 99%